Progress towards elimination of measles in Kenya, 2003-2016 - Ngina Kisangau; Kibet Sergon; Yusuf Ibrahim; Florence Yonga; Daniel Langat; Rosemary Nzunza; Peter Borus; Tura Galgalo; Sara A Lowther (The Pan African Medical Journal, 2018)

(untitled)
INTRODUCTION: Measles is targeted for elimination in the World Health Organization African Region by the year 2020. In 2011, Kenya was off track in attaining the 2012 pre-elimination goal. We describe the epidemiology of measles in Kenya and assess progress made towards elimination. METHODS: We reviewed national case-based measles surveillance and immunization data from January 2003 to December 2016. A case was confirmed if serum was positive for anti-measles IgM antibody, was epidemiologically linked to a laboratory-confirmed case or clinically compatible. Data on case-patient demographics, vaccination status, and clinical outcome and measles containing vaccine (MCV) coverage were analyzed. We calculated measles surveillance indicators and incidence, using population estimates for the respective years. RESULTS: The coverage of first dose MCV (MCV1) increased from 65% to 86% from 2003-2012, then declined to 75% in 2016. Coverage of second dose MCV (MCV2) remained 50% since introduction in 2013. During 2003-2016, 26,188 suspected measles cases were reported, with 9043 (35%) confirmed cases, and 165 deaths (case fatality rate, 1.8%). The non-measles febrile rash illness rate was consistently 2/100,000 population, and ?80% of the sub-national level investigated a case in 11 of the 14 years. National incidence ranged from 4-62/million in 2003-2006 and decreased to 3/million in 2016. The age specific incidence ranged from 1-364/million population and was highest among children aged 1 year. CONCLUSION: Kenya has made progress towards measles elimination. However, this progress remains at risk and the recent declines in MCV1 coverage and the low uptake in MCV2 could reverse these gains.